Provision of Personal Information and the Willingness-to-Pay for Receiving Critical Information in Time of an Unprecedented Disaster - Naoko Sakurai; Tokio Otsuka; Hitoshi Mitomo (International Telecommunications Society (ITS), 2017)
Followingthe Great East Japan Earthquake, information and communications technology (ICT) is expected to play an important role in future pioneeringdisaster prevention programs and post-disaster reconstruction. The increase insmartphone users allows big data to be accumulated from such diverse sourcesaspersonal information posted on social networking services(SNS), location data, and communication histories. Japan is willing to promote the useof this big data forvarious business opportunities; however,people remain anxiousabout personal information being divulged.To use big data duringdisasters, it is important to conduct research and surveys focused on Internet users'perspectives. The purpose of this paper is to analyze internet users' evaluation about providing personal information and to measure the willingness-to-pay (WTP) for receiving information services at the time of large-scale disasters. In order to quantify internet users' evaluation about providing personal information, we drew up a questionnaire and conducted a survey. To obtain more accurate and practical estimation and evaluation, we adopted the Contingent Valuation Method (CVM). To identify the factors that impacted recipients' WTP for providing personal information and to estimate the marginal contribution of each attribute to the value of WTP. We assessed the value of providing personal information at the time of large-scale disastersfor ordinary internet users quantitatively. In the case of location information, the average WTP was found to be JPY2,943. The estimated average WTP for the five cases ranged between JPY2,202 and JPY3,618, in which the highest amount was found to be for "Medical history" and the lowest for "Measurements." In order to identify the factors that impacted the respondents' WTP, we estimated the marginal contribution of the 21 attributes to the value of WTP.
Keywords: 330; Unprecedented Disaster; Personal Information; CVM; WTP; Quantitative Assessment